Age-Related Differences in Influenza B Infection by Lineage in a Community-Based Sentinel System, 2010–2011 to 2015–2016, Canada. (7th August 2017) - Skowronski, Danuta M; Chambers, Catharine; De Serres, Gaston; Sabaiduc, Suzana; Winter, Anne-Luise; Dickinson, James A; Gubbay, Jonathan B; Fonseca, Kevin; Drews, Steven J; Charest, Hugues; Martineau, Christine; Krajden, Mel; et al.
Summary: Age-related differences in influenza B lineage infection were assessed by the community-based Canadian Sentinel Practitioner Surveillance Network between 2010–2011 and 2015–2016. Influenza B(Victoria) cases were on average 20 years younger than B(Yamagata) cases, with the latter showing a bimodal age distribution. Abstract: Age-related differences in influenza B lineage detection were explored in the community-based Canadian Sentinel Practitioner Surveillance Network (SPSN) from 2010–2011 to 2015–2016. Whereas >80% of B(Victoria) cases were <40 years old, B(Yamagata) cases showed a bimodal age distribution with 27% who were <20 years old and 61% who were 30–64 years old, but with a notable gap in cases between 20 and 29 years old (4%). Overall, the median age was 20 years lower for B(Victoria) vs B(Yamagata) cases (20 vs 40 years; P < .01). Additional phylodynamic and immuno-epidemiological research is needed to understand age-related variation in influenza B risk by lineage, with potential implications for prevention and control across the lifespan.